Green Tea Dregs (Camellia sinensis (L.) Extraction Method Effect on Cutibacterium acnes and Development of Spot Cream - Arief, Maria Odelia Vania; Lieanto, Caroline; Sabani, Jessica Mei; Purwanto (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Acne is a prevalent skin health problem experienced by teenagers and adults. Green tea is one of the plants that can be used to treat acne. Green tea dregs contain catechins, which have antibacterial activity that causes acne. Objective: This study aims to determine the antibacterial activity of green tea dregs extract against Cutibacterium acnes bacteria. Methods: This study used two brewing time variations and three green tea dregs with maceration variations. The obtained extract was then analyzed for its catechin content using the total phenolic test. Section, which has a high phenolic content, was then tested for its activity against Cutibacterium acnes bacteria using the microdilution method to obtain the MIC50 value. The extract with a brewing time of 2 minutes and the ultrasonic-assisted extraction maceration method had the highest MIC50 value of 8.586 mg/mL. The MIC50 value references extract concentrations used in acne spot cream formulations. The cream obtained after the stability test is semisolid, brown, and smells like tea. Spot cream is also homogeneous and meets the pH range in cosmetic preparations of 5.5. However, the viscosity of spot cream decreased significantly after storage to 4546 cPoise from 8106 cPoise. The decrease in the viscosity of the cream was caused by the catechin content in green tea dregs extract, which is acidic, thus reducing the effectiveness of the emulator in the form of triethanolamine, which is alkaline. The decrease in viscosity of the cream also caused the spreadability of the cream to increase and the stickiness of the cream to decrease.